A comparative study of nse and bse market performance - Ruchita Nath; Zainab Khan; Shravani Kasar; Sachin Yadav (Journal of Corporate Finance Management and Banking System, 2026)
The Indian stock market plays a crucial role in the economic development of the country, with the National Stock Exchange (NSE) and the Bombay Stock Exchange (BSE) being the two major stock exchanges in India. Both exchanges contribute significantly to capital formation, liquidity, and investor participation. This study aims to conduct a comparative analysis of the market performance of NSE and BSE in order to examine their efficiency, growth trends, and stability. The study compares the benchmark indices of the two exchanges, namely NIFTY 50 and SENSEX, using secondary data collected from reliable sources such as the official websites of NSE and BSE, Reserve Bank of India publications, and financial databases. The analysis covers a period of five years and employs statistical tools such as average returns, standard deviation, percentage analysis, and graphical representation to evaluate market performance. The findings indicate that both NSE and BSE exhibit similar market movement trends as they are influenced by common economic and global factors. However, NSE demonstrates higher liquidity and trading volume, while BSE continues to maintain its significance due to its historical presence and wide listing base. The study concludes that both exchanges are efficient and play a vital role in the development of the Indian capital market.